Functional Mobility Assessment in People with Multiple Sclerosis - Ivana Sretenović; Srećko Potić; Goran Nedović; Gordana Odović; Ljiljana Šimpraga (Neurology International)
Background/Objectives: Functional mobility includes gait and balance. People with multiple sclerosis often experience gait impairment and difficulties with walking, as well as an increased risk of falling. The aim of the research was to assess functional mobility and to examine the relationship between gait and balance in people with multiple sclerosis, as well as the impact of falls on these two variables. Methods: The study sample consisted of 92 people with multiple sclerosis, with an average age of 45.10 (SD = 9.57) years, and both sexes (82.6% were female). The Activities-specific Balance Confidence Scale was used to assess an individual’s confidence in maintaining balance throughout daily activities, and the 12-item Multiple Sclerosis Walking Scale was employed to evaluate the impact of multiple sclerosis on walking ability. Descriptive statistics, measures of central tendency, Pearson’s correlations, and partial correlations were applied to the data. Results: The results indicated moderate gait impairment and a high level of function in people with multiple sclerosis. There was a correlation between confidence in maintaining balance and walking ability. Conclusions: The results of this study can be used to develop appropriate treatments and support programs for individuals with multiple sclerosis.